Decomposition of Sectoral Greenhouse Gas Emissions: A Subsystem Input-Output Model for the Republic of Ireland - TOL, RICHARD S. J. (My University, 2011)
The analysis of gas emissions by an input-output subsystem approach provides detailed insights into pollution generation in an economy by revealing the channels by which the environmental burdens are caused and transmitted throughout the production system. In this paper we propose a decomposition of the greenhouse gas emissions by using an input-output subsystems model. The empirical application is for the Irish economy, and the economic and environmental data are for year 2005. Our results show that large asymmetries exist not only in the quantitative contribution of the different activities to greenhouse gas emissions but also in the decomposed effects of this contribution.
PUBLISHED
Keywords: decomposition; Input Output Model; Ireland; data